2012
DOI: 10.1111/j.1549-8719.2012.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Induced Microvascular Recruitment in Skin and Muscle are Related and Both are Associated with Whole‐Body Glucose Uptake

Abstract: Insulin-augmented capillary recruitment in skin parallels insulin-mediated microvascular recruitment in muscle and both are related to insulin-mediated glucose uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 27 publications
3
74
1
1
Order By: Relevance
“…Regardless of the method used, insulin-stimulated microvascular changes were related to insulin-mediated glucose uptake [6]. Indeed, our results are in agreement with previous studies using contrast-enhanced ultrasound technique that showed enhanced postprandial microvascular function in healthy individuals [7] and blunted function in obese individuals [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regardless of the method used, insulin-stimulated microvascular changes were related to insulin-mediated glucose uptake [6]. Indeed, our results are in agreement with previous studies using contrast-enhanced ultrasound technique that showed enhanced postprandial microvascular function in healthy individuals [7] and blunted function in obese individuals [8].…”
Section: Discussionsupporting
confidence: 92%
“…We used capillary video microscopy, which enables direct visualisation of microvascular capillaries in the skin in a noninvasive manner. We have recently shown that insulinmediated capillary recruitment in skin parallels insulinmediated microvascular recruitment in skeletal muscle, as measured by contrast-enhanced ultrasound [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous studies, we demonstrated that the cutaneous microcirculation is a representative vascular bed to examine insulin's actions on the microcirculation. 31 Moreover, assessment of the effects of exenatide on skin microvasculature has 2 benefits. First, in contrast to measurements of muscle microcirculation, direct capillary videomicroscopy allowed us to assess the effects of exenatide not only on microvascular perfusion but also on functional capillary capacity.…”
Section: Smits Et Al Exenatide Increases Capillary Perfusion 1541mentioning
confidence: 99%
“…[2][3][4][5] It uses gas-filled microbubbles, typically with a lipid shell, that are inert, remain entirely within the vascular space, and possess an intravascular rheology similar to that of erythrocytes.…”
Section: To the Editormentioning
confidence: 99%
“…In a post hoc analysis of a recent study measuring microvascular perfusion in skeletal muscle with CEU, 5 we assessed the association of muscle microvascular perfusion with blood pressure. In this healthy, normotensive group, blood pressure was inversely related with skeletal muscle perfusion in the forearm (systolic blood pressure β=−0.50, P=0.05; diastolic blood pressure β=−0.49, P=0.03; and mean arterial pressure β=−0.53, P=0.02) after adjustment for sex and age.…”
mentioning
confidence: 99%